Q: What is -6 x -4 -8?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

-8 x 4 = -32 + 6 = -26

8 x 3/4 = 6.

6 x 8=48 48+4=52

14 + 4x - 8 = -6 4x + 6 = -6 x = (-6 + -6) / 4 x = -3

xy = 6 x + y = 8 so y = 8 - x xy = 6 substitute y with 8 - x x(8 - x) = 6 8x - x2 = 6 subtract 6 to both sides, then multiply each term by -1 x2 - 8x + 6 = 0 use the quadratic formula to find x x = (8 ± √(64 - 24)/2 x = (8 ± √40)/2 write 2 as 4 into the radical x = 8/2 ± √(40/4) x = 4 + √10 or x = 4 - √10 Therefore, the numbers are 4 + √10 and 4 - √10.

Related questions

(8 - 4) x 6 x 1 = 4 x 6 = 24

(8 x 7 x 6 x 5 x 4 x 3)/(6 x 5 x 4 x 3 x 2) = 28 combinations

x/8+6=8 I assume that we are solving for x so here goes. work backwards you have more than enough information. 8=6+(x/8) take the 6 out of the equation: 8-6=6-6=(x/8) then becomes 2=x/8 so take the 8 out of the equation: (2*8)=(x/8)8 so 2*8=16, and (x/8)8=x (as in to say that (4/2)=2, then 2*2=4 so we get back to where we started on that side; 16=x

No.

(3/4) x 8 = (8 x 3)/4 = 24/4 = 6

2 dozen = 24as does 3*8, 2*12, 1*24, 6*4, 1+23, 25-1, etc etc2 dozen =24as does 3 *8 and 4*6 and 2*12 and 1*24 and 48*0.5 etc

(2 x 3 x 4 x 5 x 6 x 7 x 8 x 9) + 1 will have a remainder of 1 when divided by 2, 3, 4, 5, 6, 7, 8, or 9. (2 x 3 x 4 x 5 x 6 x 7 x 8 x 9) + 1 = 362,881

[2/(3/4)]/6 = (2/1 x 4/3)/6 = (8/3)/(6/1) = 8/3 x 1/6 =8/18 = 4/9 ≈ 0.44

-21

Order of operations are important here and you need to work from left to right: x = 6 / 3 / 8 ; 6/3 is 2 x = 2/8 x = 1/4 x = 0.25

(3*4)+2-8 12+2-8 14-8 6

5x-4=8+2x 5x-2x=4+8 3x=12 x=12/3 x=4